IL-17 Is a Key Regulator of Mucin-Galectin-3 Interactions in Asthma - Manoj J. Mammen; Jamil Ali; Amita Aurora; Umesh C. Sharma; Ravikumar Aalinkeel; Supriya D. Mahajan; Mark Sands; Stanley A. Schwartz (International Journal of Cell Biology)
Mucus hypersecretion and chronic airway inflammation are standard characteristics of several airway diseases, such as chronic obstructive pulmonary disease and asthma. Increased mucus secretion from increased mucin gene expression in the airway epithelium is associated with poor prognosis and mortality. We previously showed that the absence of tissue inhibitor of metalloproteinase 1 (TIMP-1) enhances lung inflammation, airway hyperreactivity, and lung remodeling in asthma in an ovalbumin (OVA) asthma model of TIMP-1 knockout (TIMPKO) mice as compared to wild-type (WT) controls and mediated by increased galectin-3 (Gal-3) levels. Additionally, we have shown that in the lung epithelial cell line A549, Gal-3 inhibition increases interleukin-17 (IL-17) levels, leading to increased mucin expression in the airway epithelium. Therefore, in the current study, we further examined the relationship between Gal-3 and the production of IL-17-axis cytokines and critical members of the mucin family in the murine TIMPKO asthma model and the lung epithelium cell line A549. While Gal-3 may regulate a Th1/Th2 response, IL-17 could stimulate the mucin genes, MUC5B and MUC5AC. Gal-3 and IL-17 interactions induce mucus expression in OVA-sensitized mice. We conclude that Gal-3 may play an essential role in the pathogenesis of asthma, and modulation of Gal-3 may prove helpful in the treatment of this disease.